A rare case of mucormycosis in heart transplantation - Lalwani, Jaya; Kumar, Lokesh; ., Rameshwar; M., Jagadeesan (International Journal of Advances in Medicine, 2022)
Mucormycosis is the third most common invasive fungal infection with a high mortality rate seen in immunocompromised patients. It is an increasingly well-reported invasive fungal infection that affects recipients of solid-organ transplant. The incidence of mucormycosis in patients with heart transplants ranges from 0 to 0.6%. We reported a case of mucormycosis in a young heart transplant male recipient.